Innovations In Greek Political Communication And Consequences: Significant changes from 1981-2009 - Anastasia Deligiaouri (Estudos em Comunicação, 2011)
The introduction of new communicative ethics in politics has imposed new procedures and values in politics. The close inter-relation of media and politics has many facets and effects on the way politics is exercised and on how it is perceived by the citizens. This article investigates how new methods of political communication have been internalized into Greek media democracy, dividing the period from 1981 to the present into ﬁve periods of media democracy based on signiﬁcant events that signaled the transition towards new communicative and political ethics. A study of articles from two newspapers provides useful insights into the role of the media, especially during electoral campaigns and in politics in general. Our research also reﬂects how the speciﬁc socio-political context of the country interferes and affects the adoption of "imported" methods in political communication and how these methods affect citizens’ political behavior.